Good governance and economic development: The challenges of democratic sustainability in Nigeria - Joshua Olusegun Bolarinwa (African Journal of Governance and Development, 2013)
Perhaps the greatest problem facing Nigeria’s post-colonial state is that of democratic sustainability. Having experienced transition from colonial autocracy to independence and civil rule in 1960, Nigeria was touted as one country in sub-Saharan Africa that would likely make steady progress towards democracy and good governance. But with military intervention in politics way back on 15 January 1966, truncating the progress of the First Republic, there has been both political and governmental instability. The country has experienced the woes of bad governance, massive corruption, human rights abuses and economic deprivation from greedy civilian political leaders and military dictators. Good governance deals with the manner in which a country is governed; the process of selecting the leaders articulating national objectives; formulating policies; and the extent to which the government is performing the primary duty of advancing the welfare of its citizens. This paper examines the concept of governance and identifies the cannons of good governance. It holds that poor governance manifests itself in corruption, political instability, civil strife and conflicts, and that these impact negatively on our development efforts. It thus argues that there can be no development without good governance and recommends certain steps to enthrone good governance and enhance the welfare of the citizens, which is the ultimate goal of economic development.